THE PLACE AND ROLE OF THE LINGUO-CULTURAL STUDIES IN FOREIGN LANGUAGE TEACHING - Ivanova, Y.S.; Burmagina, L.A.; Rakhmetova, A.A. (publisher of Kostanay state pedagogical university, 2020)
This article is devoted to the important characteristics of the linguo-cultural components of the foreign language. The linguо-cultural knowledge can be got by students through original texts that contain plenty of lingua-cultural units. It highlights the peculiar usage of linguo-cultural units in everyday life. The reader can analyze the given examples of linguo-cultural units and think over their future possible usage in his speech.
Keywords: linguo-cultural studies; lingua-cultural units; language skills; communication; language development